2008
DOI: 10.1136/hrt.2008.147652
|View full text |Cite
|
Sign up to set email alerts
|

Serum intact parathyroid hormone levels predict hospitalisation for heart failure

Abstract: Serum intact PTH levels obtained in outpatients with HF were shown to be an independent predictor of hospitalisation for HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 32 publications
5
49
0
6
Order By: Relevance
“…2,8 In epidemiological studies, PTH is increased in patients with HF 9 and has shown to be independently associated with hospitalization for HF in these patients. 10 Population studies have shown PTH elevation to be associated with major risk factors for HF, including hypertension, 11 left ventricular hypertrophy (LVH), 12 atrial fibrillation (AF), 13 myocardial dysfunction (N-terminal probrain natriuretic peptide [NT-proBNP]), be associated with cardiovascular disease (CVD), many have not 18,19 ; few prospective studies have specifically examined the association between PTH and incident HF in the general population. Two prospective studies in older adults have shown PTH levels to be related to incident HF 20,21 independent of known risk factors for HF, whereas 1 study conducted in middle-aged population showed the association to be present in obese subjects only.…”
mentioning
confidence: 99%
“…2,8 In epidemiological studies, PTH is increased in patients with HF 9 and has shown to be independently associated with hospitalization for HF in these patients. 10 Population studies have shown PTH elevation to be associated with major risk factors for HF, including hypertension, 11 left ventricular hypertrophy (LVH), 12 atrial fibrillation (AF), 13 myocardial dysfunction (N-terminal probrain natriuretic peptide [NT-proBNP]), be associated with cardiovascular disease (CVD), many have not 18,19 ; few prospective studies have specifically examined the association between PTH and incident HF in the general population. Two prospective studies in older adults have shown PTH levels to be related to incident HF 20,21 independent of known risk factors for HF, whereas 1 study conducted in middle-aged population showed the association to be present in obese subjects only.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Higher circulating PTH concentrations are associated with increased risk of fracture, hypertension, left ventricular hypertrophy, and in some studies with cardiovascular mortality. [7][8][9][10][11] PTH is regulated in response to circulating calcium concentrations by the calcium-sensing receptor, which is highly expressed in parathyroid tissue. [12][13][14] PTH concentration is further modulated by calcitriol, which interacts with DNA regulatory elements via the vitamin D nuclear receptor to suppress PTH, and is an established treatment for the secondary hyperparathyroidism seen in CKD.…”
mentioning
confidence: 99%
“…188 Such studies generated a concept of "salt-aldosterone product" in the aldosterone-mediated inflammation that impairs both kidney and cardiac function. Finally, recent work has shed light on the importance of cortisol in this aldosterone-salt axis in precipitating heart failure with preserved LV ejection fraction in a mouse model of pressure overload, 189 as well as the complex interaction of parathyroid hormone, potassium, and trace elements in mediating the inflammatory state in heart failure, 190,191 which was recently reviewed by Weber and outlined in Figure 6. 192 All of these factors, in combination with high salt levels, may contribute to this therapeutic resistant state of heart failure with preserved LV ejection fraction, which if addressed at an early stage may prevent heart failure, thereby making this more of the "internists' heart failure."…”
Section: Heart Failure With Preserved LV Ejection Fractionmentioning
confidence: 99%